2015
DOI: 10.1038/ajg.2015.158
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Neuronal and Structural Changes in Submucous Ganglia of Patients With Functional Dyspepsia

Abstract: We provide the first direct evidence that FD is characterized by functional and structural abnormalities within the submucous ganglion plexus, which may be of future predictive and diagnostic value in the treatment of FD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
133
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(146 citation statements)
references
References 46 publications
7
133
0
6
Order By: Relevance
“…Duodenal eosinophilia occurs in paediatric 90 and adult functional dyspepsia 91 and is probably linked to abnormal submucosal nerve structure and impaired responsiveness of submucosal neurons 92 . Eosinophils and mast cells that degranulate next to enteric neurons provide a mechanism for sensory excitation, which can be perceived by the enteric and central nervous systems 54 .…”
Section: Gastroduodenal Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Duodenal eosinophilia occurs in paediatric 90 and adult functional dyspepsia 91 and is probably linked to abnormal submucosal nerve structure and impaired responsiveness of submucosal neurons 92 . Eosinophils and mast cells that degranulate next to enteric neurons provide a mechanism for sensory excitation, which can be perceived by the enteric and central nervous systems 54 .…”
Section: Gastroduodenal Inflammationmentioning
confidence: 99%
“…Increased CD4 + T helper 2 (T H 2) cell response is a potent producer of key cytokines (IL-4, IL-5 and IL-13) that are involved in recruiting and activating eosinophils and mast cells 97 . Eosinophil and mast cell numbers are increased in the submucosal plexus of the duodenum in patients with functional dyspepsia, and this finding was accompanied by a clear impairment of nerve excitability in the duodenal submucosal plexus -a decreased calcium response to depolarization and electrical stimulation -and could also implicate the central nervous system 54,92 . Blood-borne cytokines from the gut can also signal in the brain, thereby enabling cross-talk between the immune system, brain and gut 54 .…”
Section: Gastroduodenal Inflammationmentioning
confidence: 99%
“…In a recent study, 5 patients with Los Angeles Grade C oesophagitis were given proton pump inhibitors (PPIs). Oesophageal biopsies were evaluated using a 0-3 scale for epithelial inflammation, basal cell and papillary hyperplasia, and spongiosis.…”
Section: Acknowledgementmentioning
confidence: 99%
“…Functional dyspepsia according to the Rome IV diagnostic criteria [4] comprises postprandial distress syndrome (bothersome postprandial fullness or early satiety severe enough to impact on regular activities for 3 or more days per week in the past 3 months) or the epigastric pain syndrome (bothersome epigastric pain or epigastric burning 1 or more days per week in the past 3 months), although many patients complain of both syndromes [4]. Recent evidence has identified duodenal inflammation in functional dyspepsia, with a small but significant increase in eosinophils in the duodenal mucosa (and in some cases mast cells), most notably in subjects with early satiety and postprandial distress [5,6].…”
mentioning
confidence: 99%
“…Histamine 2 receptor antagonists (H 2 RAs), a small portion of claims implicating acid suppression, were mostly associated with concerns of limited or absent efficacy, or a false-positive drug screen. A meta-analysis based on older studies suggested that H 2 RA therapy is efficacious in functional dyspepsia [21], of interest as more recently duodenal eosinophilia and increased mast cells (that may release histamine) [5,6] or duodenal changes in the microbiome that might release excess histamine [22] suggest that antagonizing histamine might do more good than just reduce gastric acid secretion [1]. Histamine antagonism may thus be an alternative therapy in functional dyspepsia with equal efficacy and lower risk of adverse events than with other drugs.…”
mentioning
confidence: 99%